Transboundary Haze-Free for Southeast Asian Countries by 2020: A Delusional Vision? - Nurhidayatuloh,; Febrian,; Apriandi, Mada; Y. , Annalisa; Primadianti Sulistyaningrum, Helena; Handayani, Irawati; Zuhro, Fatimatuz; Kadir Jaelani , Abdul; Tedjomurti, Kukuh (International Journal of Psychosocial Rehabilitation, 2020)
The Transboundary Haze-Free ASEAN by 2020 is a vision as a result of the 11th COPAATHP. This vision is followed up at the 12th COP by adopting the roadmap on ASEAN cooperation, which has eight items used as a strategic, action-oriented, and time-bound framework. However, it seems that these steps are far from effective. The will in the agreement is not necessarily accompanied by the willingness and ability of the state in the implementation. Moreover, the absence of a dispute resolution mechanism also becomes the main concern of this agreement. The strategy that has been well designed in its implementation becomes toothless because it collides with the principles of sovereignty, non-interference, and domestic policies that cannot be touched by the ASEAN community. This article aims to provide a clear picture of the AATHP after Indonesia is effectively bound by the agreement and provides a critique of the development of the agreement in the COP forum. The study argues that there needs to be an additional protocol, especially with regard to dispute resolution mechanisms, so that there will be legal certainty when a country refuses to be bound and ignores this agreement. In the sense that it is not a country that can be prosecuted and sanctioned when land and forest fires occur within their territory, but the reluctance of a country to coordinate and receive assistance from the parties, which must be resolved because it is not in accordance with the objectives.